Pengaruh Budaya Organisasi terhadap Kinerja Dosen PTS di Provinsi Riau (Program Studi Akuntansi Dan Manajemen) - Afrijal, Afrijal (Komunitas Manajemen Kompetitif, 2015)
Abstract: Lecturers are professional educators and scientists with the main task of transforming, develop and disseminate science, technology, and art through education, research, and community service. But still questioned regarding the performance of lecturers who are still not optimal, and also at private universities, especially the economic field in this case is the accounting and management still has an organizational culture that tend to be less conducive. Is this lack of conducive organizational culture influences the performance of lecturers in the works. Campus culture conducive proved a significant influence (sign value = 0.000) and positive (value b = 0.886) on the performance of private lecturer especially those working in the accounting and management courses in Riau province. This result proves that the more conducive campus culture will increasingly meninggkat private lecturer performance. Keywords: lecturer Performance, Organizational Cultur